Utilisation of bamboo leaves as carbon/silica precursor to convert polymer waste into 2-chloroethyl benzoate - Mohd Alwi, Nurnabihah (2018)
Bamboo leaves is an abundant agro-waste which often being buried in landfill for the disposal or being incinerated. Polysorbate 20 was categorized as a polymer waste and act as a substrate which usually used as a stabilizer in food industry. The aim of this study is to transform waste into potential catalyst in order to reduce the abundance of waste problem. This study presents an ecological way in utilising the bamboo leaves to generate carbon/silica with a simple method. The carbon/silica were obtained by carbonising the bamboo leaves at 300°C, 350°C, 400°C and 450°C. Different carbonisation temperature affected the physicochemical properties of catalyst. Carbon/silica composites acted as heterogeneous solid acid catalyst in the production of 2-chloroethyl benzoate where Polysorbate 20 undergone catalytic reaction with benzoyl chloride. The sulfonated carbon/silica can be produced by sulfuric acid treatment by introducing the sulfonic acid group on the graphite sheet. The characterisation was performed by using XRD, FT-IR and TGA to study the physicochemical properties of SO3HC/Si02 Results from XRD demonstrated that the samples were amorphous. From TGA, the ratio of SO3H-C/Si02 was increased with the increasing of carbonisation temperature. The absorbance of functional groups such as COOH, S=0 and C=C were decreased as the temperature decreased which verified by FTIR. The best catalyst for the reaction of Polysorbate 20 with benzoyl chloride was SO3HC/Sio2- 350°C with 99% of Polysorbate 20 conversion and 3.4% yield of 2-chloroethyl benzoate.